Reviews. Issue 2 (1st October 2015) - Pardoe, Sheila; Whitley, Leila
Caribbean Spaces: Esc apes from Twilight Zones, Carole Boyce Davies (2013) Urbana, Chicago and Springfield: University of Illinois Press, 250 pp., ISBN: 9780252079535, £18.49Dest ination It aly: Representing Migration in Contemporary Media and Narrative, Emma Bond, Guido Bonsaver, Federico Faloppa (2015) Oxford, Bern, Berlin, Bruxelles, Frankfurt am Main, New York, Wien: Peter Lang, 467 pp., ISBN: 9783034309615, £45.00